Service composition for end-users - Hylli, Otto; Lahtinen, Samuel; Ruokonen, Anna; Systä, Kari (Acta Cybernetica, 2014)
RESTful services are becoming a popular technology for providing and consuming cloud services. The idea of cloud computing is based on on-demand services and their agile usage. This implies that also personal service compositions and workflows should be supported. Some approaches for RESTful service compositions have been proposed. In practice, such compositions typically present mashup applications, which are composed in an ad-hoc manner. In addition, such approaches and tools are mainly targeted for programmers rather than end-users. In this paper, a user-driven approach for reusable RESTful service compositions is presented. Such compositions can be executed once or they can be configured to be executed repeatedly, for example, to get newest updates from a service once a week.